Análise dos critérios de priorização de projeto junto ao fundo estadual de recursos hídricos do Estado de São Paulo: estudo de caso do Comitê da Bacia Hidrográfica do Tietê-Jacaré - Martins, Renata Genova (2012)
The State Water Resources Fund of São Paulo (FEHIDRO) was established by the 7.633 State Law, of December 30 of 1991, to give financial support to the hydrographic basins actions. The resources from this fund are distributed in the Water Basis Committees (CBH) every year, each CBH is responsible for finding the way to select the projects. This research aimed to study the criteria and rules for distribution of financial resources in the Water Basis Committee Tietê-Jacaré (CBH-TJ), arising from FEHIDRO, aiming to contribute to its improvement. For develop of this study four stages were performed: Bibliographic Search; Chacterization of study area; Documental Search and survey of opinion. The third stage consisted in a diagnosis of the investments realized with FEHIDRO resources and also the comparative analysis of the adopted criteria to the projects approval in the CBH-TJ and other committees of São Paulo State. The last stage referred to the questionnaires along the keymembers of the committee, where it sought the identification of process failures, difficulties in the projects evaluation and guidelines for solving the problems and/or contributions for the process improvement. The results showed that some criteria adopted by CBH-TJ have failures (lack of information to the score, absence of weighing and subjective criteria which makes difficult the impersonality in the assessments). It was suggested several ways to improve the process (adoption of more technical criteria that reduct the subjective in the assessments, elaboration of specific punctuation score cards according each thematic line, addition of new criteria, increase of the evaluation time of projects and weight attribution for all criteria), which will give support for the improvement of the decisions to be made by CBH-TJ, as well contribute for a better allocation of FEHIDRO public resources.